Liver cT1 decreases following direct acting antiviral therapy in patients with chronic hepatitis C virus - Jayaswal, A; Levick, C; Collier, J; Tunnicliffe, E; Kelly, M; Neubauer, S; Pavlides, M (Springer, 2020)
Purpose Direct-acting antiviral therapies (DAAs) for treatment of chronic hepatitis C virus (HCV) have excellent rates of viral eradication, but their effect on regression of liver fibrosis is unclear. The primary aim was to use magnetic resonance imaging (MRI) and spectroscopy (MRS) to evaluate changes in liver fibrosis, liver fat and liver iron content (LIC) in patients with chronic HCV following treatment with DAAs.